Basic approach to melanonychia: a review - Aseri, Jatin; Kumawat, Kanchan; Tamta, Aatish; Bhargava, Puneet; Meena, Ram Singh (International Journal of Research in Dermatology, 2022)
Melanonychia is a brownish-black staining of the nail plate. It can affect a single or several nails on both the fingers and toes. Melanocytic activation and melanocytic hyperplasia are the two basic mechanisms involved in the development of melanonychia. Melanocytic activation occurs as enhanced melanic pigmentation of the nail matrix epithelium and nail plate without a corresponding rise in the number of melanocytes, resulting in melanonychia. The number of matrix melanocytes increases in melanocytic hyperplasia. Involvement of a pathogen has also been suggested as a mechanism for its development. A thorough clinical history should be taken, including questions regarding various triggers and causal events, as well as the use of a questionnaire. A proper detailed physical examination is of a great need to properly identify the type of melanonychia and to rule out melanoma which is of great importance in clinical practice. Onychoscopy and nail biopsy also acts as an aid in proper diagnosis of melanonychia. Treatment of melanonychia basically depends on the underlying etiology. One major aim is to rule out melanoma if present and its proper management in time.